2008
DOI: 10.1017/s0950268808001568
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and clearance of differentSalmonellaserovars in buildings housing laying hens

Abstract: We investigated factors associated with persistence of different Salmonella serovars in buildings housing laying hens in Great Britain using survival analysis. A total of 264 incidents of Salmonella detection occurring between July 1998 and August 2007 in 152 houses were recorded. For incidents involving Salmonella Enteritidis (SE), both the rodent score of the house and the type of house were positively associated with persistence. For non-SE serovars, only the type of house was associated with persistence. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 26 publications
1
52
1
1
Order By: Relevance
“…Out of the 154 poultry farms screened in the present study, 11 farms were found to be positive for NTS incidence that had overcrowding, poor farm hygiene, lack of adequate biosecurity measures and infestation of rodents and insects. Mice, wild birds, ants and snakes are known to play important role in the transmission of Salmonella among birds, flocks and farms [28][29][30]. Hence, there is an association between the farm hygiene and incidence of NTS in poultry farms.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 154 poultry farms screened in the present study, 11 farms were found to be positive for NTS incidence that had overcrowding, poor farm hygiene, lack of adequate biosecurity measures and infestation of rodents and insects. Mice, wild birds, ants and snakes are known to play important role in the transmission of Salmonella among birds, flocks and farms [28][29][30]. Hence, there is an association between the farm hygiene and incidence of NTS in poultry farms.…”
Section: Discussionmentioning
confidence: 99%
“…The role of rodents, flies, beetles and wild birds as vectors in Salmonella spp. transfer is extensively discussed (14)(15)(16)(17). Stress has an immunosuppressive effect in egg laying hens, which can have negative consequences with respect to salmonellosis and shedding (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate the spread of pathogens by horizontal transmission, but it is difficult to establish the source of contamination (Hinton 1988). Since the persistence of Salmonella in the environment is an important feature in its epidemiology, hens may be infected during growing phase (Carrique-Mas et al 2009), by being in contact with inoculated hens (Thomas et al 2009), with confirm the complex epidemiology of Salmonella infections (Hinton 1988).…”
Section: Resultsmentioning
confidence: 97%
“…One of the factors that facilitate the proliferation of flies is the accumulation of large amounts of manure (Carrique-Mas et al 2009). When these flies are exposed to Salmonella contaminated environments, they may become infected and transmit the bacteria to housed poultry (Holt et al 2007).…”
Section: Resultsmentioning
confidence: 99%